Ocean Modelling - Ocean Modelling (Elsevier, 2026)
Ocean Modelling is an international journal that highlights the significant findings and breakthroughs in all aspects of ocean modelling research to support the advancement of ocean sciences. Ocean Modelling welcomes submissions in various forms of mechanism analysis, laboratory experiments, ocean model development, improvements and applications, as well as model-observation synergies. In particular, ocean model applications at different scales that aim at understanding the ocean and Earth system and its coupling to biological, geological and chemical systems are welcome. Special attention can be also given to interdisciplinary contributions focusing on interactions between physics, biology and chemistry, cross-scale processes, and machine learning.
FI 0.89
Q2
Keywords: Earth; Space & Environmental Sciences; Oceanography & Paleoceanography; Oceanografía; Paleoceanografía; Acuerdos transformativos; Transformative agreements; Modelos de circulación oceánica; Modelos del sistema terrestre